The new world of economics : explorations into the human experience - Tullock, Gordon; McKenzie, Richard B. (Homewood, Ill. : R.D. Irwin, 1985)
This book attempts to break out of the narrow confines of economic subject matter and to seek out new refreshing problems that can be dealt with in a simpler way. In this edition, more topics have been expatiated on, such as the new emerging field of socio-biology; current public-policy issues like taxes, supply-side economics, and rent seeking.
Includes bibliographical references and index.
ne 25/06/2021
Loans
Keywords: Economics; Social sciences